Centella Asiatica, Collagen Density, and MMP-1: A Review of Photoaging and Skin Repair Evidence - Valentinus Ferdian Cipta; Agus Eka Darwinata; Bagus Komang Satriyasa (Riviera Publishing, 2026)
Centella asiatica is a medicinal plant widely investigated for dermatological and cosmeceutical applications, particularly in wound healing, anti-aging, collagen remodeling, and protection against ultraviolet-induced skin damage. This review analyzes recent studies published between 2021 and 2025, focusing on the relationship between Centella asiatica, collagen density, collagen synthesis, and matrix metalloproteinase-1 (MMP-1), a major collagen-degrading enzyme involved in skin photoaging. The reviewed evidence shows that C. asiatica and its major triterpenoid compounds—including asiaticoside, madecassoside, asiatic acid, and madecassic acid—support dermal matrix preservation through antioxidant activity, fibroblast stimulation, increased collagen production, and downregulation of matrix-degrading enzymes. Direct in vivo evidence indicates that topical C. asiatica cream may improve collagen density and influence MMP-1 expression in UVB-exposed skin. Additional studies using fibroblast models, nanoformulations, wound healing systems, and clinical skin-aging preparations support its role in improving collagen biosynthesis and skin structural recovery. However, the evidence remains heterogeneous, as many studies evaluate collagen markers or general MMP activity rather than MMP-1 specifically. Future research should prioritize standardized extracts, direct measurement of MMP-1, collagen type I/III expression, collagen density, and well-controlled human trials.